Epistemologi Tafsir Ilmi dalam Tafsir Al-Muntakhab - Udin Saprudin (Lembaga Yasin AlSys, 2025)
Although tafsir ilmi (scientific exegesis) in Qur’anic studies has received considerable attention, research specifically examining the epistemology of tafsir ilmi in Tafsir Al-Muntakhab remains limited. This study aims to investigate the epistemology of tafsir ilmi in Tafsir Al-Muntakhab, particularly with regard to its sources, methods, and interpretive validity. Adopting a qualitative approach with a library research design, the study draws on classical and modern exegetical texts as data sources, collected through documentation techniques and analyzed using descriptive analysis. The findings show that Tafsir Al-Muntakhab employs a scientific approach in interpreting verses of Al-Qur’an by utilizing scientific theories to reveal the truth of the Qur’anic miracles, thereby presenting a form of tafsir ilmi that seeks to integrate revelation and scientific knowledge. These results contribute to the development of theories of scientific exegesis and broaden understanding of how scientific knowledge is applied in Qur’anic interpretation. The study concludes that a strong epistemological foundation for tafsir ilmi is crucial for enhancing Muslims’ understanding of the miraculous nature of Al-Qur’an in the context of science, and recommends the integration of scientific approaches into exegesis studies within educational institutions and curriculum policy. The implications of this research include theoretical contributions to enriching the literature on Qur’anic exegesis and practical implications for developing more science-based religious education, while also opening avenues for further exploration of the application of scientific theories in Qur’anic interpretation.